The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.chest.2021.06.083
|View full text |Cite
|
Sign up to set email alerts
|

Optimal NIV Medicare Access Promotion: Patients With Hypoventilation Syndromes

Abstract: The existing coverage criteria for home noninvasive ventilation (NIV) do not recognize the diversity of hypoventilation syndromes and advances in technologies. This document summarizes the work of the hypoventilation syndromes Technical Expert Panel working group. The most pressing current coverage barriers identified were: (1) overreliance on arterial blood gases (particularly during sleep); (2) need to perform testing on prescribed oxygen; (3) requiring a sleep study to rule out OSA as the cause of sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…98 In 2021, the Optimal NIV Medicare Access Promotion (ONMAP) technical expert panel representing the American Thoracic Society, the American College of Chest Physicians, the American Association of Respiratory Care, and the American Academy of Sleep Medicine published consensus recommendations for updating CMS coverage criteria for noninvasive positive pressure ventilation devices. 99,100 Noteworthy among the recommendations are increasing the qualifying vital capacity threshold to <80% predicted if accompanied by respiratory symptoms, and acceptance of an end-tidal or transcutaneous PCO2 as a substitute for arterial puncture to document hypercapnia. Recommendations of the expert panel for thoracic restrictive diseases are detailed in Table 4.…”
Section: Indications For Initiation Of Nocturnal Noninvasive Ventilationmentioning
confidence: 99%
“…98 In 2021, the Optimal NIV Medicare Access Promotion (ONMAP) technical expert panel representing the American Thoracic Society, the American College of Chest Physicians, the American Association of Respiratory Care, and the American Academy of Sleep Medicine published consensus recommendations for updating CMS coverage criteria for noninvasive positive pressure ventilation devices. 99,100 Noteworthy among the recommendations are increasing the qualifying vital capacity threshold to <80% predicted if accompanied by respiratory symptoms, and acceptance of an end-tidal or transcutaneous PCO2 as a substitute for arterial puncture to document hypercapnia. Recommendations of the expert panel for thoracic restrictive diseases are detailed in Table 4.…”
Section: Indications For Initiation Of Nocturnal Noninvasive Ventilationmentioning
confidence: 99%
“…Furthermore, in line with previous EUROVENT data [1], other chronic lung diseases are treated with HMV. Despite guidelines [3,5] stating that carbon dioxide measurements (arterial blood gas or transcutaneous) are mandated in order to make a diagnosis of nocturnal hypoventilation-with recent data highlighting a targeted reduction in daytime and nocturnal carbon dioxide levels improving the patients' clinical outcome [6,7,[16][17][18][19][20]-the current survey showed that when initiating HMV and prior to discharge post initiation, the SpO 2 monitoring and physiological and ventilator downloaded data were employed more frequently than carbon dioxide measurements. Surprisingly, some respondents reported that they never use carbon dioxide measurements to titrate HMV.…”
Section: Tools To Assess Monitor and Manage Nocturnal Hypoventilationmentioning
confidence: 99%
“…Diagnosis of hypoventilation is often delayed or missed [120], and patients experience increased healthcare utilization leading up to diagnosis than matched controls [121]. Observational data primarily focusing on obesity hypoventilation suggest that patients with hypoventilation syndromes in the hospital should be empirically started on PAP therapy to reduce mortality (4.9% vs. 22.7% at six months) and risk of readmission [122][123][124].…”
Section: Osa and Hypoventilation Syndromesmentioning
confidence: 99%